2022
DOI: 10.1093/geront/gnac096
|View full text |Cite|
|
Sign up to set email alerts
|

A Citation Review of 83 Dissemination and Implementation Theories, Models, or Frameworks Utilized in U.S.-Based Aging Research

Abstract: Background and objectives Dissemination-implementation.org outlines 110 Theories, Models, and Frameworks (TMFs): we conducted a citation analysis on 83 TMFs, searching Web of Science and PubMed databases. Research design and methods Search terms were broad and included “aging,” “older,” “elderly” and “geriatric.” We extracted how each TMF in identified articles from inception through January 28, 2022. Included articles must h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
5
1
0
Order By: Relevance
“…We identified that the CFIR 202 and iPARIHS 214 were among the most used frameworks. This was also consistent with the findings of Sullivan et al 213 However, these authors also identified another commonly used framework (Greenhalgh's Diffusion of Innovation in Service Organizations 215 ) that we did not. We also identified Normalization Process Theory 216 among the most common, which Sullivan et al also did not.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We identified that the CFIR 202 and iPARIHS 214 were among the most used frameworks. This was also consistent with the findings of Sullivan et al 213 However, these authors also identified another commonly used framework (Greenhalgh's Diffusion of Innovation in Service Organizations 215 ) that we did not. We also identified Normalization Process Theory 216 among the most common, which Sullivan et al also did not.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with those of Sullivan et al, 213 whose citation review identified low but increasing use of implementation theories, models, and frameworks in aging research (not necessarily in the aged care setting) in the USA. Our study builds on this work by examining the aged care context specifically, and including studies from any country.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although there appeared to be no difference in the effectiveness of interventions that did versus did not use such a theory, framework or model, their use facilitates a thorough exploration of factors that led or did not lead to an effective intervention. Furthermore, the use of these theories, frameworks and models can guide successful implementation, adaptation and dissemination of interventions and should be applied in future efforts 64–66. One excellent example is provided by the intervention reported by Pinto et al 67 who included their TIDieR checklist68 in their published manuscript.…”
Section: Discussionmentioning
confidence: 99%